2013
DOI: 10.1166/jbt.2013.1103
|View full text |Cite
|
Sign up to set email alerts
|

A Sulfated Nanofibrous Mesh Supporting the Osteogenic Differentiation of Periosteum-Derived Cells

Abstract: The periosteum is a thin fibrous membrane covering the surface of long bone and is known to play a critical role in bone development and adult bone fracture healing. Loss or damage of the periosteum tissue during traumatic long bone injuries can lead to retarded healing of bone graft-mediated repair. The regenerative potential of periosteum-derived progenitor cells (PDCs) has inspired their use as an alternative to bone marrow-derived mesenchymal stromal cells (MSCs) to augment scaffold-assisted bone repair. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…BMSCs and PDCs were isolated as described previously [ 32 ] from long bones of either freshly diabetic BBDP rats, those with more extended T1DM (blood glucose maintained at 250–500 mg/dl, ~100 days), or healthy nondiabetic male Wistar rats (~100 days old; Charles River Lab). Wistar rats were chosen as normal nondiabetic controls because the BBDP rats were derived from the Wistar strain [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BMSCs and PDCs were isolated as described previously [ 32 ] from long bones of either freshly diabetic BBDP rats, those with more extended T1DM (blood glucose maintained at 250–500 mg/dl, ~100 days), or healthy nondiabetic male Wistar rats (~100 days old; Charles River Lab). Wistar rats were chosen as normal nondiabetic controls because the BBDP rats were derived from the Wistar strain [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Staining was also carried out on cells cultured in both high and normal glucose expansion media (negative control). After photo-documentation of the alizarin red and oil red staining, the dye was released for quantitation per the literature protocol [ 32 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The R f and R r were determined based on the second cycle using Equation ( 1) and (2). Charles River SASCO SD rats by enzymatic digestion in MEM (without ascorbic acid) solution of 2.5-mg/mL type 2 collagenase (Worthington, Lakewood, NJ) as previously described [44] . Cells were pelleted, resuspended and expanded in MEM without ascorbic acid supplemented with 20% FBS (Hyclone) and 2% L-glutamine, and 1% penicillin-streptomycin (expansion media).…”
Section: Stress-controlled Cyclic Thermal Mechanicalmentioning
confidence: 99%
“…Periosteum plays a crucial role in the fracture healing process, especially during the secondary callus formation. Periosteum-derived cells (PDCs) have a strong potential for proliferation and osteogenic differentiation, and they are essential for the healing and repair of bone fractures and defects [5]. Previous studies have shown that PDCs can repair a critical size long-bone defect in mice.…”
Section: Introductionmentioning
confidence: 99%